2017
DOI: 10.1038/srep46748
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica glycoconjugates immuneregulate dendritic cells through the Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin inducing T cell anergy

Abstract: Dendritic cell-specific ICAM-3 grabbing non-integrin (DC-SIGN) expressed on a variety of DCs, is a C-type lectin receptor that recognizes glycans on a diverse range of pathogens, including parasites. The interaction of DC-SIGN with pathogens triggers specific signaling events that modulate DC-maturation and activity and regulate T-cell activation by DCs. In this work we evaluate whether F. hepatica glycans can immune modulate DCs via DC-SIGN. We demonstrate that DC-SIGN interacts with F. hepatica glycoconjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…In turn, S. mansoni PMPs may be potent inducers of the mammalian immune system perhaps via an IgE‐mediated immune response during parasitic infections (van Remoortere et al ., ). Species within Fasciola , a genus of trematodes commonly known as liver flukes and also classified as flatworms, also express PMGs (Glycans #2a/b, #4, #10b, and #12) (Garcia‐Campos et al ., ; Rodríguez et al ., ). Interestingly, α‐fucosylated and α‐mannosylated epitopes of PMGs produced by Fasciola hepatica and other helminths are reportedly ligands of the immune‐modulatory dendritic cell‐specific intercellular adhesion molecule‐3‐grabbing non‐integrin (DC‐SIGN), a well‐studied C‐type lectin (van Die et al ., ; Meyer‐Wentrup et al ., ; Rodriguez et al ., 2017).…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 97%
“…In turn, S. mansoni PMPs may be potent inducers of the mammalian immune system perhaps via an IgE‐mediated immune response during parasitic infections (van Remoortere et al ., ). Species within Fasciola , a genus of trematodes commonly known as liver flukes and also classified as flatworms, also express PMGs (Glycans #2a/b, #4, #10b, and #12) (Garcia‐Campos et al ., ; Rodríguez et al ., ). Interestingly, α‐fucosylated and α‐mannosylated epitopes of PMGs produced by Fasciola hepatica and other helminths are reportedly ligands of the immune‐modulatory dendritic cell‐specific intercellular adhesion molecule‐3‐grabbing non‐integrin (DC‐SIGN), a well‐studied C‐type lectin (van Die et al ., ; Meyer‐Wentrup et al ., ; Rodriguez et al ., 2017).…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 97%
“…CLRs have also been suggested to associate with induction of Th2 responses by Toxocara -derived antigens ( 99 ). Among them, DC-SIGN is one of the most important receptors in recognition of T. canis, F. hepatica , and B. malayi -derived glycan products shaping the immune response toward a Th2/regulatory state ( 100 102 ). Rodríguez and colleagues have recently found that DC-SIGN plays a central role in priming Treg upon interaction with F. hepatica -derived glycans ( 102 ).…”
Section: Helminth-derived Products (Hdps) As Potent Immunomodulatorsmentioning
confidence: 99%
“…Among them, DC-SIGN is one of the most important receptors in recognition of T. canis, F. hepatica , and B. malayi -derived glycan products shaping the immune response toward a Th2/regulatory state ( 100 102 ). Rodríguez and colleagues have recently found that DC-SIGN plays a central role in priming Treg upon interaction with F. hepatica -derived glycans ( 102 ). The presence of mannose and fucose residues in F. hepatica -glycoconjugates can facilitate DC-SIGN stimulation and trigger intracellular pathway enabling DCs to prime Treg and inhibit proliferation of allogeneic T cells ( 102 ).…”
Section: Helminth-derived Products (Hdps) As Potent Immunomodulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, it has been reported that FhTeg induces DC modulation, resulting in a lack of T cell Th1 cytokine response and proliferation [21]. In addition, the glycan products produced by F. hepatica participate in the modulation of DC maturation and mediate the production of IL-10 and IL-4 during infection, inducing a Th2/regulatory-polarized immune response [22][23][24][25]. F. hepatica can also induce the development of phenotypes that are characterized by a decreased production of proinflammatory cytokines, as well as the expression of general markers that are characteristic of an M2 macrophage phenotype and have been shown to promote the differentiation of Th2 and Treg cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%